1992
DOI: 10.1093/aje/136.7.843
|View full text |Cite
|
Sign up to set email alerts
|

Lymphohematopoietic Cancer in Styrene-Butadiene Polymerization Workers

Abstract: 1,3-Butadiene and styrene are suspected carcinogens and common chemicals used in the synthesis of rubber. To investigate any potential human hazards from exposure to these chemicals, a case-control study of 59 lymphohematopoietic cancers was conducted within a cohort of male workers employed between 1943 and 1982 in eight North American styrene-butadiene rubber polymer-producing plants. A total of 193 controls were matched to the cases by plant, age, year of hire, duration worked, and survival to time of death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 0 publications
2
75
1
Order By: Relevance
“…In this study, racemic DEB (DL, a 1:1 mixture of R/R and S/S isomers) was used. 4 The structures of P4-1 and P4-2 were prematurely characterized previously as 2′-deoxy-N-(2-hydroxy-1-oxiranylethyl)guanosine based on limited NMR data (18). Their structures were corrected based upon the results of the present study.…”
Section: Ms-ms Tandem Mass Spectrometrymentioning
confidence: 97%
“…In this study, racemic DEB (DL, a 1:1 mixture of R/R and S/S isomers) was used. 4 The structures of P4-1 and P4-2 were prematurely characterized previously as 2′-deoxy-N-(2-hydroxy-1-oxiranylethyl)guanosine based on limited NMR data (18). Their structures were corrected based upon the results of the present study.…”
Section: Ms-ms Tandem Mass Spectrometrymentioning
confidence: 97%
“…1 Recently, 1,3-butadiene was reclassified as a "known human carcinogen" 2 based on epidemiologic and mechanistic information. Exposure to 1,3-butadiene is associated with lymphosarcoma 3,4 and leukemia [5][6][7][8] in occupationally exposed workers. Benzene also has been long established as a known human carcinogen.…”
Section: Introductionmentioning
confidence: 99%
“…A. The 1 H NMR spectrum of the P8-dG cross-linking product in DMSO-d 6 . Inset: The signal between 10 and 11 ppm; B.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1 H NMR spectrum of the P8-dG cross-linking product in DMSO-d 6 (Figure 4A), the broad signal at 10.74 ppm with one proton (Figure 4A, inset) was assigned to the N1 proton. The presence of an N1 proton indicated that this cross-linking product was indeed an N1-N7 cross-linking product as suggested above.…”
Section: Structural Characterization Of the Cross-linking Products Ofmentioning
confidence: 99%
See 1 more Smart Citation